Features and management of osteoarthritis from the perspective of individuals with osteoarthritis: A systematic review of qualitative studies - Sylvain Mathieu; Alice Courties; Céline Mathy; Serge Perrot; Françoise Alliot Launois; Stanislas Moumbe; Nathan Foulquier; Jérémie Sellam; Rinie Geenen (Osteoarthritis and Cartilage Open)
Objective: To enable person-centered care, considering beliefs, needs, and priorities of individuals with osteoarthritis (OA) is crucial. Nevertheless, concepts that they consider important are not fully recapitulated in assessment and care. The aim of this study was to clarify how individuals with OA conceive, experience, and manage their OA and pain. Design: A systematic literature review was conducted including qualitative studies (interviews, focus groups, open questionnaires) regardless of OA joint location. Verbatim quotations relating to OA and OA-related pain were collected and merged in codes. Themes and categories relating to these codes were defined. Results: The seven databases yielded a total of 9585 studies of which 79 qualitative studies were selected. Analysis of 667 verbatim quotations of 2009 participants led to 117 codes and 24 themes. Themes were grouped into 2 categories, ‘features’ and ‘management’. ‘Features’ encompassed experiences ranging from common challenges (e.g., adjust to reduced function) to high impact outcomes needing therapeutic attention (e.g., devastating pain). The ‘management’ category captured positive and negative conceptions associated with pharmacological and cognitive-behavioral self-management, psychoeducation, and interventions. Themes from both categories were classified into four domains: symptoms, functioning, psychological, and social. A fifth domain ‘disease’ was also used to categorize the themes under ‘features’. Conclusions: Several themes reported by OA individuals are hardly represented in current assessment and recommendations, e.g., fatigue, sleep disturbance, psychosocial impact, and effects on family and caregivers. The reviewed beliefs, needs, and priorities may support individualized screening, complement existing assessment instruments, and can help refine interventions and psychoeducational materials.